Perception of Loudness Is Influenced by Emotion - Asutay, Erkin; Västfjäll, Daniel (PLOS ONE, 2012)
Loudness perception is thought to be a modular system that is unaffected by other brain systems. We tested the hypothesis that loudness perception can be influenced by negative affect using a conditioning paradigm, where some auditory stimuli were paired with aversive experiences while others were not. We found that the same auditory stimulus was reported as being louder, more negative and fear-inducing when it was conditioned with an aversive experience, compared to when it was used as a control stimulus. This result provides support for an important role of emotion in auditory perception.